Upaya Pengelolaan Lingkungan Akibat Bencana Banjir di Kecamatan Empang, Kabupaten Sumbawa: Environmental Management Efforts Due to Flood Disasters in Empang District, Sumbawa Regency - Utama, Pramudya Bagas; Nursahida, Nisa; Adi, Angga Satria; Revanka, Fazal Shinwary (Media Ilmiah Teknik Lingkungan (MITL), 2024)
Indonesia is a country that is prone to natural disasters from a geological perspective. Based on information from the Head of the Information Data Center and Public Relations of the National Disaster Management Agency, natural disaster trends have increased by 350% in the last three decades. A significant increase is hydrometeorological disasters which are influenced by weather aspects, such as floods, landslides, tornadoes, and droughts. Sumbawa Regency is one of the areas in Indonesia that is being hit by an increasing trend of natural disasters. The most recent natural disaster that hit one of the Sumbawa Regency areas was the flood disaster in Empang District. The cause of flooding itself can occur due to various things both natural and human. Floods can be caused by natural events such as rainfall over a long period of time, soil flooding leaving only rocks, and no water absorption. Therefore it is essential to analyze the flood disaster that occurred in Empang District so that a good environmental management strategy can be carried out. The management carried out is to restore environmental functions that have been lost due to damage caused by the disaster. Installing drainage and implementing the Internet of Things in overcoming flooding is considered to be quite effective. The relocation and reclamation activities of corn plantation areas carried out by bioremediation and revegetation processes can improve land conditions.